Development and Validation of a Spinsterhood Anxiety Scale for Diagnosing Anxiety among Unmarried Arab Girls - Aldahadha, Basim; Al Dwakat, Mohammad (Islamic Guidance and Counseling Journal, 2026)
This study aimed to develop a tool to diagnose spinsterhood anxiety among Muslim girls. A group of experts (n=26) evaluated these items to verify content validity. The items were shortened to 29 items. Two separate samples were subsequently selected: the first was used for exploratory factor analysis (EFA), while the second was used for confirmatory factor analysis (CFA). The results revealed that 26 items explained five factors, representing 72.30% of the total variance. These factors were named family, personal, physical, sexual, and financial. The results also showed that the CFA provided positive confirmation of convergent validity and reliability, with significant evidence to support these statistics for the relationships between the Spinsterhood Anxiety Scale (SAS and the Beck Depression Inventory Arabic Version (BDI-ArV), Beck Anxiety Inventory Arabic Version (BAI-ArV), Well-Being (WB), and Arab Scale of Mental Health (ArS-MH) scales. Cronbach's alpha values for the five factors ranged between 0.88 and 0.75, while the total score was 0.91. The correlations between the SAS and the five factors were also significant. The scale predicted 79% of all BDI-ArV, BAI-ArV, WB, and ArS-MH. The study concluded that the SAS has suitable psychometric properties for diagnosis.